Pectoralis Major Muscle Rupture – Review of Treatment Options - Wiater, Zuzanna; Dziegciarczyk, Anna; Włodarczyk, Aleksandra; Swoboda, Kamil; Borówka, Karolina; Brankowska, Karolina; Jakubowska, Marta; Olejnik, Michał; Tymińska, Paulina; Kądziołka, Witold Jerzy (Quality in Sport, 2026)
Introduction In recent decades, the incidence of pectoralis major (PM) ruptures has risen, largely due to the increased popularity of high-intensity weight training and the use of anabolic steroids among athletes. Failing to address a PM rupture can result in permanent physical deformity and long-term functional impairment. While early detection and prompt surgical intervention often simplify the repair process and improve success rates, modern reconstructive advancements now allow for effective treatment even in chronic cases. Aim of study This review aims to evaluate the current state of knowledge regarding the anatomy, diagnostic metrics, and both operative and non-operative treatment options for acute and chronic pectoralis major ruptures. State of knowledge Pectoralis major (PM) ruptures primarily affect men between the ages of 20 and 40. Patients often report hearing an audible "pop" or experiencing a distinct tearing sensation at the moment of injury. If left unaddressed, these injuries progress into a chronic state. While the medical literature lacks a single, universal definition for chronic PM ruptures, the typical threshold used is six weeks following the initial trauma. Summary (conclusion) Conservative, non-surgical treatment of PM ruptures is generally limited to elderly or low-demand individuals, specific partial tears, or patients with medical contraindications to surgery. In contrast, surgical intervention is considered the gold standard, as it consistently produces the most favorable clinical and cosmetic results. While acute injuries typically allow for a straightforward direct repair, chronic cases are more complex and often require surgeons to utilize autografts or allografts to bridge retracted tissue. Despite these technical challenges, surgical treatment for chronic injuries remains highly recommended, as patients can still achieve high levels of satisfaction and functional recovery.